SUDDHI WADHANI DALAM UPACARA PERKAWINAN DI DESA SIBETAN KECAMATAN BEBANDEM KABUPATEN KARANGASEM (PERSPEKTIF PENDIDIKAN AGAMA HINDU) - Ida Ayu Putu Mila Witantari, I Ketut Dani Budiantara, Wayan Yanik Yasmini (Widya Aksara, 2020)
In Sibetan Village there was a marriage between Hindus and non-Hindus. The marriage ceremony is held after the bride and groom hold the Sudhiwadani Ceremony. The Sudhiwadani ceremony has not been clearly understood by the Sibetan Village Manners. In this regard, research was conducted with the aim of: (1) describing the procession of the Sudhiwadan Ceremony in the marriage ceremony in Sibetan Village, (2) knowing the function of the Sudhiwadani Ceremony in the marriage ceremony in the Sibetan Village, and (3) knowing the value of the Hindu religious ceremony at the Sibhi Wadhani Ceremony in the ceremonial ceremony of Sibetan, (2) marriage in Sibetan Village. The study uses qualitative data types, primary and secondary data sources. The research instrument was in the form of interview guidelines, with a purposive informant determination technique. Data were collected by techniques: (1) observation, (2) interviews, (3) documentation, and (4) literature. Research findings: (1) Sudhiwadani Ceremony procession in a marriage ceremony in Sibetan Village includes Preparation: making a statement of adherence to Hinduism, a letter of request to PHDI Karangasem Regency for dedication, completed with a photo, preparing a photo copy of KTP, and determining witnesses. The ceremony: The reading of the statement, the signing of the Sudhiwadani Certificate, the implementation of the mabyakala ceremony, maprayascita and prayers. (2) Function of Sudhiwadani Ceremony: self-purification and endorsement, changing the status of religion and the agreement of the bride and bridegroom. (3) The values ??of Hindu religious education contained in the Sudhiwadani Ceremony are: tattwa values, namely Widhi Tattwa and Karmaphala Tattwa, moral values, namely behaving well according to the Tri Rich Parisudha teachings, and ritual values, namely the implementation of ceremonies ranging from mabyakala to worship and worship. continued with the marriage ceremony, carried out based on purity, sincerity and the stability of faith in Hyang Widhi.